2011
DOI: 10.1105/tpc.111.089771
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone Biosynthesis in Medicago  truncatula and Rice Requires the Symbiotic GRAS-Type Transcription Factors NSP1 and NSP2  

Abstract: Legume GRAS (GAI, RGA, SCR)-type transcription factors NODULATION SIGNALING PATHWAY1 (NSP1) and NSP2 are essential for rhizobium Nod factor-induced nodulation. Both proteins are considered to be Nod factor response factors regulating gene expression after symbiotic signaling. However, legume NSP1 and NSP2 can be functionally replaced by nonlegume orthologs, including rice (Oryza sativa) NSP1 and NSP2, indicating that both proteins are functionally conserved in higher plants. Here, we show that NSP1 and NSP2 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
239
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 292 publications
(255 citation statements)
references
References 57 publications
6
239
0
2
Order By: Relevance
“…Pea (Pisum sativum) mutants deficient in BRs or GA had reduced nodulation (Ferguson et al, 2005), and SL levels were positively correlated with nodulation in pea and L. japonicus (Soto et al, 2010;Foo and Davies, 2011;Foo and Reid, 2013;Liu et al, 2013), but infection was not characterized in these studies. Our observation that CCD8 is induced in root hairs by S. meliloti taken together with the identification of SLs in M. truncatula root exudates (Liu et al, 2011) raises the possibility that SLs are secreted during infection. Therefore, SLs may either act as an additional cue for rhizobia in the rhizosphere, as seen with mycorrhization (Akiyama et al, 2005), or they may induce developmental changes in root hairs during infection, perhaps analogous to their role in induction of lateral root formation.…”
Section: Discussionmentioning
confidence: 56%
“…Pea (Pisum sativum) mutants deficient in BRs or GA had reduced nodulation (Ferguson et al, 2005), and SL levels were positively correlated with nodulation in pea and L. japonicus (Soto et al, 2010;Foo and Davies, 2011;Foo and Reid, 2013;Liu et al, 2013), but infection was not characterized in these studies. Our observation that CCD8 is induced in root hairs by S. meliloti taken together with the identification of SLs in M. truncatula root exudates (Liu et al, 2011) raises the possibility that SLs are secreted during infection. Therefore, SLs may either act as an additional cue for rhizobia in the rhizosphere, as seen with mycorrhization (Akiyama et al, 2005), or they may induce developmental changes in root hairs during infection, perhaps analogous to their role in induction of lateral root formation.…”
Section: Discussionmentioning
confidence: 56%
“…GRAS-domain proteins have already been shown to function during AM associations, with RAM1 playing a major role [6], and NSP1/NSP2 playing minor roles [7][8]. We found that OsRAM1 can complement Medicago ram1, indicating that OsRAM1 served the same function as MtRAM1 during mycorrhizal colonization (Supplementary information, Figure S7).…”
Section: Dear Editormentioning
confidence: 51%
“…Isolation, identification and quantification of petunia strigolactones. Plants were grown in an X-Stream 20 aeroponic system (Nutriculture) as previously described for Medicago truncatula 47 . From day 8 until day 12, exudates were collected and pooled, and root material was sampled.…”
Section: Methodsmentioning
confidence: 99%